Mengurai Kompleksitas Komunikasi Interpersonal: Sintesis Faktor Psikologis, Sosial, dan Kontekstual dari Tinjauan Literatur - Tasya Eka Damayanti; Kani Dwiharyani; Anita Yasmin (MUKASI: Jurnal Ilmu Komunikasi, 2025)
Background: Interpersonal communication is very important in various aspects of life. This is because the benefits of interpersonal communication include: increasing comfort, increasing harmony, can make individuals receive and disclose information voluntarily, honestly, and without coercion. However, achieving effective interpersonal communication is not easy. There are several factors that can influence interpersonal communication. Research Method: This research method is a literature review using Google Scholar. The results of the study are presented in a qualitative descriptive manner. Results: The results of this study indicate that factors that can influence interpersonal communication are: empathy, supportive attitude, openness, equality and positive attitude, democratic parenting, self-concept, self-control, interpersonal viewing, social media use, self-confidence, self-esteem, sociodrama technique group guidance services, phubbing behavior, and self-disclosure. Conclusion: Empathy, supportive attitude, openness, equality and positive attitude, democratic parenting, self-concept, self-control, interpersonal observation, social media use, self-confidence, self-esteem, sociodrama technique group guidance services, phubbing behavior, and self-disclosure influence the effectiveness of interpersonal communication.